2014
DOI: 10.1002/chem.201404965
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Supramolecular Synthons in Designing Gelators Derived from Multiple Drugs

Abstract: A simple strategy for designing salt-based supramolecular gelators comprised of various nonsteroidal anti-inflammatory drugs (NSAIDs) and amantadine (AMN) (an antiviral drug) has been demonstrated using a supramolecular synthon approach. Single-crystal and powder X-ray diffraction established the existence of the well-studied gel-forming 1D supramolecular synthon, namely, primary ammonium monocarboxylate (PAM) synthon in all the salts. Remarkably five out of six salts were found to be capable of gelling methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…MTT assay in RAW 264.7 cell line indicated that G78 had even better biocompatibility compared to the parent drug DIC (IC 50 > 1 m m and < 1 m m for G78 and DIC , respectively); subsequent PGE 2 assay (in RAW 264.7) revealed that anti‐inflammatory response of G78 was nearly comparable to its parent drug ( DIC ). Therefore, methyl salicylate gel of G78 could, in principle, be used for combination therapy ( Figure ) …”
Section: Designing Lmwgsmentioning
confidence: 99%
“…MTT assay in RAW 264.7 cell line indicated that G78 had even better biocompatibility compared to the parent drug DIC (IC 50 > 1 m m and < 1 m m for G78 and DIC , respectively); subsequent PGE 2 assay (in RAW 264.7) revealed that anti‐inflammatory response of G78 was nearly comparable to its parent drug ( DIC ). Therefore, methyl salicylate gel of G78 could, in principle, be used for combination therapy ( Figure ) …”
Section: Designing Lmwgsmentioning
confidence: 99%
“…In this endeavour, we have successfully employed supramolecular synthons in the context of crystal engineering to design LMWGs capable of displaying various functional properties including self‐delivery applications . We recently exploited primary ammonium monocarboxylate (PAM) synthons, which are among the most successful gel‐inducing supramolecular synthons developed by us, to develop supramolecular topical gels for combination therapy …”
Section: Introductionmentioning
confidence: 99%
“…The driving force for the self‐assembly process is the successful combination of various specific intermolecular interactions, the shape of molecules, concentration, temperature, etc . It is necessary to understand the mechanistic pathway from isolated molecules to primary or secondary aggregates and supramolecular gel architectures via spontaneous nucleation and growth . Mode of self‐ assembly has a profound influence on the functional properties such as anisotropic strength, structural stability, material transport and optoelectronic properties and a thorough understanding of which is necessary for practical applications .…”
Section: Introductionmentioning
confidence: 99%